Evaluation by remote sensing of the expansion of the Palcacocha Lake and glacial retreat in the Cordillera Blanca –Peru. (LACCEI, 2024)
The increasing formation of glacial lakes and their expansion in recent years increases the risk of alluviums due to glacial lakes outburst floods in high tropical mountains, such as the one that destroyed part of the city of Huaraz in 1941 in the Cordillera Blanca, of the central Andes of Peru. Given the danger faced by the more than 130,000 people who inhabit the alluvial fan of Quilcay River, were analyzed the interannual variation of the surface of the Palcacocha Lake, the glacial surface of its micro-basin and the variation of the surrounding climate between the years 1984 and 2022, to determine the relationships that would exist between these variables, as an indicator of the risk of flooding due to overflow of the lake. For this, the surface of the lakes and the area of the glacier were calculated with multispectral Landsat images and compared with the result of the processing of meteorological data from the Recuay, Milpo, and Anta stations, using the data obtained from the Google Earth Engine application and data reported in bibliographic sources, for validation. A period of strong expansion of the lake was found until 2012 and a trend of loss of glacier surface0 in addition, to a strong relationship between the expansion of the Palcacocha lake and the annual increase in global mean temperature. Likewise, a strong El Niño-Southern Oscillation event led to the growth of Lake Palcacocha due to increased rainfall and greater glacier retreat.